(untitled) (Research, Society and Development, 2022)
The multiplicity of sociocultural groups that integrate the educational space is a reality present in Brazilian schools. Despite this reality, there is no adequate approach regarding pedagogical practices about cultural differences in school daily life, especially because there is no teacher training leading to a deeper understanding of this subject. It is in this universe that the present paper is situated. In this sense, we aim to analyze teaching knowledge necessary for teacher training to act interculturally. This research follows a qualitative approach. We use literature review based on studies from authors who discuss teacher training, such as Selma Garrido Pimenta (2012) and Miguel González Arroyo (2008, 2013, 2014a, 2014b), and those who address the issue of interculturality in educational practices, such as: Vera Maria Candau (2008, 2012, 2014, 2016), Nilma Nilo Gomes (2007) and Reinaldo Matias Fleuri (2018a, 2018b). We conclude by emphasizing that to advance in this perspective, it is necessary to include the study of interculturality, among the essential knowledge in the processes of teacher training to support democratic pedagogical practices.